The Influence of Wordwall Learning Media and Learning Interest on Learning Outcomes - Zunidar Zunidar; Suwandi Suwandi (Yayasan Keluarga Guru Mandiri, 2025)
Technology integration into teaching has become increasingly important in modern education, especially in improving student engagement and achievement. This research explores the effect of Wordwall-based learning media on ninth-grade student learning outcomes in the Indonesian language at MA Laboratory UIN SU Medan. While previous studies have shown the advantages of digital learning tools, there is still limited understanding of their specific influence on learning interest and performance in various educational settings. This quantitative quasi-experimental study fills this gap by examining how Wordwall media and students' learning interests influence academic achievement. Data were gathered through pretests and posttests and then analyzed using statistical methods to assess significance. The results show that Wordwall usage significantly boosts student outcomes, with a clear difference between the experimental and control groups (Fcalculated = 30.855, p 0.05). Additionally, students with higher learning interests performed better, and a positive interaction was found between Wordwall usage and learning interest (Fcalculated = 4.629, p 0.05). These findings indicate that Wordwall enhances student learning interests and learning outcomes, making it a valuable learning media for educators seeking to improve learning outcomes.